OPTIMALISASI PENGGUNAAN WHATSAPP SEBAGAI ALAT MANAJEMEN KEARSIPAN DI KALANGAN MAHASISWA - Mohammad Ricky Ramadhan Rasyid (Program Studi Ilmu Komputer FMIPA-UHO, 2024)
This study aims to analyze students' perceptions of using WhatsApp as a tool for archival management by applying the Technology Acceptance Model (TAM). The research measures four variables: Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, and Behavioral Intention to Use. A quantitative approach using a survey method was employed, involving 88 students from the Library and Information Science program at Universitas Halu Oleo, class of 2024. The research instrument consisted of a questionnaire utilizing a Likert scale to evaluate students' perceptions of the ease and benefits of using WhatsApp. The findings indicate that the Perceived Usefulness and Perceived Ease of Use variables have an average score of 3.7, categorized as optimal. Meanwhile, the Attitude Toward Using variable achieved a mean of 3.5, also classified as optimal. However, the Behavioral Intention to Use variable showed an average score of 3.4, which has not yet reached the optimal category. Overall, WhatsApp is perceived as a beneficial and easy-to-use tool, though there is room for improvement in fostering a stronger intention to use it consistently.